Community Empowerment Through Waste Management With Reduce, Reuse and Recycle System (3r) In Bulota Village - Ilham, Asni; Rahman, Misran; Tune Sumar, Warni (Green Publisher, 2022)
Waste processing in Bulota Village, Talaga Jaya District is very necessary considering the limited infrastructure and waste processing facilities in the surrounding area, which are unable to contain existing waste processing. This demonstrates the paucity of garbage processing facilities and residents' lack of waste sorting knowledge (organic and inorganic). The impact is that a lot of paper and plastic waste accumulates into useless waste. One of the waste management models is the 3R system, namely Reuse, Reduce and Recycle. Waste will have various negative and very large impacts if the handling is not carried out carefully and seriously. This results in changes in the environmental balance that are detrimental to the community. The results of observations carried out by the service team from the State University of Gorontalo in the field show that most of the total The head of the family and surrounding villagers in Bulota Village have not been able to separate waste (organic and inorganic) due to limited public knowledge and level of understanding of waste accumulation.